Analisis Efisiensi Waktu Kerja dan Kinerja SDM pada Proses Skiving di Industri Mebel Skala Kecil - Foci, Nia; Yasin, Muhamad; Munanda, M. Arif (LPPM-ITEBA, 2025)
This study aims to analyze work time efficiency and evaluate employee performance in the skiving process at Juned Furniture Home Industry, Pasuruan. The method employed was work sampling, with a total of 54 observations conducted on employee work activities. The results show that 89% of the time was used productively, while the remaining 11% was classified as idle. Data adequacy and uniformity tests confirmed that the number of observations met the required statistical standards. Performance evaluation using the Westinghouse Performance Rating System yielded a correction factor of +0.18, resulting in a rating factor of 1.18. This indicates that the human resources involved in the skiving process demonstrated a good level of quantitative performance. Allowance time was calculated at 9.5% of total working hours, which remains within an acceptable range. The calculation of standard time and output revealed a productivity rate of 0.15 chair designs per hour. These findings are expected to serve as a practical reference for managerial decision-making regarding work efficiency and production capacity planning in small and medium-sized furniture industries.